SWOT Analysis: Marketing Strategy of Apotek Sawojajar Mas to Increase Sales And Competitiveness - Isti Fadah; Siti Indah Purwaning Yuwana (Journal of Management and Business Innovations, 2022)
The change in the service orientation of the pharmaceutical industry from product-oriented to patient-oriented and the high public need for pharmaceutical products, especially after Indonesia experienced the COVID-19 pandemic, became an excellent opportunity for the development of the pharmacy business in Indonesia. Apotek Sawojajar Mas is one of the pharmacies in Malang City which has had an increased turnover in the last three years through the pandemic. The rapid development of the number of pharmacies in the city of Malang gives people many choices. The intense competition in the pharmacy requires owners to think of innovative strategies to increase sales and competitiveness. This study aimed to analyze the SWOT strategy to increase the sales and competitiveness of Apotek Sawojajar Mas. Data was collected through documentation, field observations, and interviews with pharmacy owners, employees, and consumers. The results show that Apotek Sawojajar Mas is in the first quadrant, which means it can implement the SO strategy to increase sales. The results of this study provide views to other pharmacy businesses on what strategic factors need to be improved and replaced to increase competitiveness in seizing the market in Malang City.Keywords: Competitiveness, pharmacy, sales, strategy, SWOT